PERBANDINGAN METODE SAW (SIMPLE ADDITIVE WEIGTHING) DAN AHP (ANALITYC HIERARCHY PROCESS) PADA SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN RUMAH READY-LIMITED DI PERUMAHAN STUDI KASUS: KOTA SEMARANG - Amartya, Deva Nur; Diartono, Dwi Agus (MEANS (Media Informasi Analisa dan Sistem), 2023)
Home is a necessity that must be owned by everyone in this day and age. In the past, this house was built by the owner himself, but over time, many housing developers have provided alternatives. This housing developer provides ready-to-occupy houses to be directly occupied by buyers. However, with the increasing number of housing options, prospective buyers must observe very carefully and be careful in choosing a ready-to-live-in house. Prospective buyers must have some special criteria or a helper to determine this house. With this, there will be a system that helps to make choices using two methods, namely the Simple Additive Weighting (SAW) method, often known as the weighted addition method. The basic concept of the Simple Additive Weighting ( SAW ) method is to find a weighted sum with a performance rating of each alternative on all attributes. While the method of Analytic Hierarchy Process (AHP).